Physical activity and preschool children: Preschool teachers’ perceptions - Senol, Fatma Betul (Southeast Asia Early Childhood Journal, 2021)
In this study, it is aimed to understand the perceptions of preschool teachers around the physical activity levels of children in preschool period and the factors that increase or limit their physical activity. The case study design, one of the qualitative research methods, was used in the study. In addition to maximum variation sampling from purposeful sampling types was used in the selection of the study group. A total of 102 teachers, out of 296 teachers, working in 85 schools were reached. The semi-structured interview form prepared by the researcher was used as the data collection tool. As a result of this study, it was seen that most of preschool teachers had positive opinions about physical activity, they gave importance to physical activity in their classroom activities, and they applied physical activity regularly and in a systematic plan. Preschool teachers are aware of the contribution and importance of physical activity to children, and it is thought that if arrangements are made in line with their suggestions to perform physical activity, children will be more physically active. Teachers made suggestions to improve physical conditions, to have regular PA, to direct them to sports, to ensure that children exercise at home with family education, and to plan the plans interesting so that they can include more PA and make children more physically active. Policy makers, healthcare providers, and teachers should take into account these recommendations and provide various supports to increase children’s PA levels.